Penguatan Karakter Peserta Didik melalui Pendidikan Kewarganegaraan - Khadiza Rahma; Syamzaimar Syamzaimar (Jurnal Pendidikan dan Kewarganegara Indonesia, 2026)
The era of globalization presents challenges of moral degradation among students, including intolerance, individualism, and declining nationalism. These issues make character strengthening through Civic Education (PKn) a national priority. This study aims to analyze the effectiveness of PKn in shaping students’ character, particularly the values of religiosity, nationalism, independence, mutual cooperation, and integrity. The research employed a qualitative Library research design using secondary data from 18 scientific journals and 2 books published between 2021 and 2026. Data were collected through literature review and analyzed using content and thematic analysis to identify patterns of PKn implementation and its impact. The findings indicate that PKn effectively develops Good citizenship through character education based on Pancasila. Effective strategies include teacher role modeling, Problem-Based Learning (PBL), and digital media such as infographics and gamification. These approaches were reported to improve empathy, national loyalty, and integrity among students. The Merdeka Curriculum further supports character development by emphasizing affective learning through authentic projects. Challenges arising from foreign cultural influences can be addressed through collaboration among schools, families, and communities. The study concludes that PKn plays a significant role in strengthening students’ character and supporting the realization of Golden Indonesia 2045 through sustainable character education.